Novel cyclic voltammetry behavior of 3-((benzothiazol-2- diazenylnaphthalene-2,7-diol and use it for spectrophotometric determination of copper (II )in honey sample - Khazaal, Fatma .A.; Mohammed, Hussein. J.; M.Radhi, Muhammed . (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
The azo reagent 3-((benzothiazol-2-diazenylnaphthalene-2,7-diol] was synthesized and characterized by FT-IR ,1H-NMR and 13CNMR spectral techniques. The electrochemical behavior of the azo reagent and its complex with Cu (II) has been studied at glassy carbon disk GCE electrode in different supporting electrolyte at concentration (1M) and scan rate (100mv.s-1). Spectrophotometric determination of copper (II ) is based on the formation of a 2:1 complex with above reagent. The complex has Î»max at(588) nm and Ômax of( 1.436x104)L.mol-1.cm-1 . A linear correlation (0.1 â€“ 3.0 Î¼g. ml-1) was found between absorbance at Î»max and concentration . The effect of diverse ions on the determination of copper (II) to investigate the selectivity of the method were also studied . The stability constant of the product was (1.1x108 ) . The proposed method was successfully applied to the analysis of honey sample .